Development and Validation of a Small Animal Immobilizer and Positioning System for the Study of Delivery of Intracranial and Extracranial Radiotherapy Using the Gamma Knife System. (April 2017) - Awan, Musaddiq J.; Dorth, Jennifer; Mani, Arvind; Kim, Haksoo; Zheng, Yiran; Mislmani, Mazen; Welford, Scott; Yuan, Jiankui; Wessels, Barry W.; Lo, Simon S.; Letterio, John; Machtay, Mitchell; et al.
The purpose of this research is to establish a process of irradiating mice using the Gamma Knife as a versatile system for small animal irradiation and to validate accurate intracranial and extracranial dose delivery using this system. A stereotactic immobilization device was developed for small animals for the Gamma Knife head frame allowing for isocentric dose delivery. Intercranial positional reproducibility of a reference point from a primary reference animal was verified on an additional mouse. Extracranial positional reproducibility of the mouse aorta was verified using 3 mice. Accurate dose delivery was validated using film and thermoluminescent dosimeter measurements with a solid water phantom. Gamma Knife plans were developed to irradiate intracranial and extracranial targets. Mice were irradiated validating successful targeted radiation dose delivery. Intramouse positional variability of the right mandible reference point across 10 micro-computed tomography scans was 0.65 ± 0.48 mm. Intermouse positional reproducibility across 2 mice at the same reference point was 0.76 ± 0.46 mm. The accuracy of dose delivery was 0.67 ± 0.29 mm and 1.01 ± 0.43 mm in the coronal and sagittal planes, respectively. The planned dose delivered to a mouse phantom was 2 Gy at the 50% isodose with a measured thermoluminescent dosimeter dose of 2.9 ± 0.3 Gy. The phosphorylated form of member X of histone family H2A (γH2AX) staining of irradiated mouse brain and mouse aorta demonstrated adjacent tissue sparing. In conclusion, our system for preclinical studies of small animal irradiation using the Gamma Knife is able to accurately deliver intracranial and extracranial targeted focal radiation allowing for preclinical experiments studying focal radiation.